Novel aspects of the molecular mechanisms controlling insulin secretion. - Eliasson, L; Abdulkader, F; Braun, M; Galvanovskis, J; Hoppa, M; Rorsman, P (2008)
Pancreatic beta-cells secrete insulin by Ca(2+)-dependent exocytosis of secretory granules. beta-cell exocytosis involves SNARE (soluble NSF-attachment protein receptor) proteins similar to those controlling neurotransmitter release and depends on the close association of L-type Ca(2+) channels and granules. In most cases, the secretory granules fuse individually but there is ultrastructural and biophysical evidence of multivesicular exocytosis. Estimates of the secretory rate in beta-cells in intact islets indicate a release rate of approximately 15 granules per beta-cell per second, 100-fold higher than that observed in biochemical assays. Single-vesicle capacitance measurements reveal that the diameter of the fusion pore connecting the granule lumen with the exterior is approximately 1.4 nm. This is considerably smaller than the size of insulin and membrane fusion is therefore not obligatorily associated with release of the cargo, a feature that may contribute to the different rates of secretion detected by the biochemical and biophysical measurements. However, small molecules like ATP and GABA, which are stored together with insulin in the granules, are small enough to be released via the narrow fusion pore, which accordingly functions as a molecular sieve. We finally consider the possibility that defective fusion pore expansion accounts for the decrease in insulin secretion observed in pathophysiological states including long-term exposure to lipids.